2013
DOI: 10.1128/jvi.00743-13
|View full text |Cite
|
Sign up to set email alerts
|

The Resistance Protein Tm-1 Inhibits Formation of a Tomato Mosaic Virus Replication Protein-Host Membrane Protein Complex

Abstract: The Tm-1 gene of tomato confers resistance to Tomato mosaic virus (ToMV). Tm-1 encodes a protein that binds ToMV replication proteins and inhibits the RNA-dependent RNA replication of ToMV. The replication proteins of resistance-breaking mutants of ToMV do not bind Tm-1, indicating that the binding is important for inhibition. In this study, we analyzed how Tm-1 inhibits ToMV RNA replication in a cell-free system using evacuolated tobacco protoplast extracts. In this system, ToMV RNA replication is catalyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 52 publications
1
21
0
1
Order By: Relevance
“…At this point, the binding of replication proteins to the membrane is so strong that the association is maintained in a buffer containing 0.5-M (or even 1-M) NaCl (58,104), at which point most peripheral membrane proteins dissociate from the membranes. Through analysis of Tm-1, a protein inhibitor of ToMV RNA replication, it was suggested that the replication proteins first bind to membranes in a 0.5-M NaCl-sensitive manner and then form a complex with TOM1, TOM2A, and ARL8 to establish 0.5-M NaCl-resistant membrane binding (see Tm-1: An Inhibitor of Tobamovirus RNA Replication) (58). During these processes, the genomic RNA becomes resistant to nucleases in the absence, but not in the presence, of detergents (58).…”
Section: Premembrane-targeting Complex Recruitment To Membranes and Cmentioning
confidence: 99%
“…At this point, the binding of replication proteins to the membrane is so strong that the association is maintained in a buffer containing 0.5-M (or even 1-M) NaCl (58,104), at which point most peripheral membrane proteins dissociate from the membranes. Through analysis of Tm-1, a protein inhibitor of ToMV RNA replication, it was suggested that the replication proteins first bind to membranes in a 0.5-M NaCl-sensitive manner and then form a complex with TOM1, TOM2A, and ARL8 to establish 0.5-M NaCl-resistant membrane binding (see Tm-1: An Inhibitor of Tobamovirus RNA Replication) (58). During these processes, the genomic RNA becomes resistant to nucleases in the absence, but not in the presence, of detergents (58).…”
Section: Premembrane-targeting Complex Recruitment To Membranes and Cmentioning
confidence: 99%
“…We proposed that ToMV-Hel must undergo a conformational change to interact with host factors during the assembly of the replication complex (27). In a cell-free replication system, Tm-1 inhibits the binding of replication proteins to the host membrane proteins TOM1 and ARL8 and the sequestration of replication templates, which are tightly linked to and precede the formation of the replication complex, in the membranous compartment (14). How partial inhibition of helicase NTPase activity affects overall replication, or if other mechanisms (e.g., inhibition of a conformational change required for replication complex assembly) also contribute to the inhibition by Tm-1 will be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the aforementioned domains, the 183-kDa protein also contains the RNA-dependent RNA polymerase domain in the read-through region. Tm-1 inhibits the formation of ToMV replication complexes on host intracellular membranes and consequently inhibits negative-strand viral RNA synthesis (14). The amino acid changes found in Tm-1 resistance-breaking mutants locate at the helicase domain of ToMV replication proteins (ToMV-Hel) and decrease the affinity of Tm-1 for the replication proteins (12).…”
Section: Significancementioning
confidence: 99%
“…The Tm-1-encoded product interacts directly with the viral replicase, impairing viral genome replication (Ishibashi and Ishikawa, 2013).…”
Section: Effector-triggered Immunity: Intracellular Immune Receptor Rmentioning
confidence: 99%